IMPORTANT CLINICAL FEATURES OF LAYMBLIOSIS IN CHILDREN - Sanokulova Sitora Avazovna (Galaxy International Interdisciplinary Research Journal, 2023)
Lambliosis, also known as giardiasis, is a common parasitic infection caused by the protozoan Giardia lamblia. It affects both adults and children, with an estimated 200 million cases worldwide. Lambliosis in children can cause a range of clinical features, including diarrhea, abdominal pain, and malabsorption. The purpose of this article is to review the important clinical features of lambliosis in children.